Managerial Competence in Achieving Unqualified Opinion (UQO) in East Kalimantan Province - Indonesia - La Ode Hasiara; Sudarlan Sudarlan; Ahyar Muhammad Diah (Soshum: Jurnal Sosial dan Humaniora, 2019)
The objectives of this study are (1) to explore competencies of the state apparatus as key informants related to the acquisition of UQO in the East Kalimantan Province of Indonesia and (2) to explore competencies related to (a) competent leaders, (b ) competency of leaders, (c) leaders with clear vision, mission, goals, and objectives, and (d) collaborative competencies. The method of the study is interpretive descriptive qualitative employing the researchers as the main research instrument, and then assisted by key informants. To test the validity of the data, (a) confirmation, (b) verification, and (c) data validation is conducted. The results of this research are drawn based on observations, interviews, documentation, and triangulation; all show that (1) leaders must be competent and become role models for subordinates so UQO can be achieved well and (2) in addition to being competent, leaders must also have the needed competency to support UQO’s achievements, for example (a) having the same vision, (b) having the same mission, (c) having the same goals, and (d) having the same objectives to win UQO in East Kalimantan Province. The conclusion is that UQO can be achieved well if the leaders (management) of the organization become a good role model and exemplary for subordinates.